The Boatman's Tale: The Buried Giant and Cosmopolitanism in Crisis. Issue 7 (3rd October 2022) - Stacy, Ivan
ABSTRACT: Ishiguro abandoned his familiar mode of unreliable, first-person narration in The Buried Giant . This article argues that this formal shift is the culmination of an increasing tendency to deny consolation to his protagonists, a move that represents an increasingly critical and reflective stance towards cosmopolitan values. The article begins by drawing on Stoic thought to outline the relationship between consolation and cosmopolitanism, and by positing a distinction between professions of openness towards others and a genuine ability to engage and negotiate with difference. The first half of the article proper argues that Ishiguro's early narrators were only superficially cosmopolitan; however, from When We Were Orphans onwards, the fact that consolation is denied to the protagonists prompts a more transformative engagement with the world. The second half of the article argues that these tendencies reach a fuller stage of development in The Buried Giant, with the presence of a third-person narrator impelling the protagonists to reconsider their personal situations within the context of universal aspects of human experience; in this way, the novel advocates genuinely transformative cosmopolitanism.